2022
DOI: 10.1158/2326-6066.cir-21-0853
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming CAR-Mediated CD19 Downmodulation and Leukemia Relapse with T Lymphocytes Secreting Anti-CD19 T-cell Engagers

Abstract: Chimeric antigen receptor (CAR)–modified T cells have revolutionized the treatment of CD19-positive hematologic malignancies. Although anti-CD19 CAR-engineered autologous T cells can induce remission in patients with B-cell acute lymphoblastic leukemia, a large subset relapse, most of them with CD19-positive disease. Therefore, new therapeutic strategies are clearly needed. Here, we report a comprehensive study comparing engineered T cells either expressing a second-generation anti-CD19 CAR (CAR-T19) or secret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 35 publications
6
29
0
Order By: Relevance
“…The TCE led to a similar CD3ε and F-actin organization at the IS compared to that observed in TCR-stimulated Jukat cells while actin clearance and CD3ε distribution in CAR-T Jurkat cells were not properly organized [ 63 ]. Importantly, similar results were also observed when primary cells were used [ 61 ]. Therefore, this analysis indicates a higher quality of the IS assembled by TCEs in comparison to CAR-T cells.…”
Section: Bsabs Versus Carssupporting
confidence: 79%
See 1 more Smart Citation
“…The TCE led to a similar CD3ε and F-actin organization at the IS compared to that observed in TCR-stimulated Jukat cells while actin clearance and CD3ε distribution in CAR-T Jurkat cells were not properly organized [ 63 ]. Importantly, similar results were also observed when primary cells were used [ 61 ]. Therefore, this analysis indicates a higher quality of the IS assembled by TCEs in comparison to CAR-T cells.…”
Section: Bsabs Versus Carssupporting
confidence: 79%
“…We also have previously shown efficient activating signaling in addition to the polarization of F-actin and CD3ε to the IS induced by an anti-epidermal growth factor receptor (EGFR) and anti-CD19 TCE. The organized IS showed a similar topology to antigen-stimulated IS and correlated with efficient T cell activation in vitro and in vivo [ 61 , 62 , 63 ]. Therefore, TCE-mediated T cell redirection seems to induce the assembly of a canonical IS, as well as effective T cell activating signaling and function similar to events induced during antigen stimulation of T cells.…”
Section: T Cell Is Organization and Effector Function Induced By Bsabmentioning
confidence: 99%
“… 34–40 Our previous work in B-ALL showed that CD19-STAb T cell therapy could prevent CD19 downregulation and subsequent tumor escape more efficiently and at lower E:T ratios than CD19-CAR T cells. 30 41 In contrast, loss of CD1a expression was not detected on cell surface of target cells co-cultured with either CD1a-CAR or CD1a-STAb T cells. These differences may be attributable to the impact that the density and biology of the targeted antigen plays on T cell activation.…”
Section: Discussionmentioning
confidence: 91%
“…STAb T cells represent a next-generation T cell-redirecting immunotherapy for B-ALL 30 and coT-ALL, being easily applicable to other cancers for which a suitable immunotherapy target is available. 23 A major advantage for STAb T cells over CAR T cells lies in the fact that an effective treatment with STAb T cells might require lower T cell doses, which could be of particular relevance when an adequate number of mature effector T cells cannot be engineered due to either the lymphopenic status of many multi-treated patients or manufacturing constrains in patients with aggressive and hyperleukocytic relapses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation